Market entry waves and volatility outbursts in stock markets - Ivonne Blaurock; Noemi Schmitt; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2017)
We develop a simple agent-based financial market model in which speculators' market entry decisions are subject to herding behavior and market risk. Moreover, speculators' orders depend on price trends, market misalignments and fundamental news. Using a mix of analytical and numerical tools, we show that a herding-induced market entry wave may amplify excess demand, triggering lasting volatility outbursts. Eventually, however, higher stock market risk reduces stock market participation and volatility decreases again. Simulations furthermore reveal that our approach is also able to produce bubbles and crashes, excess volatility, fat-tailed return distributions and serially uncorrelated price changes.
Keywords: C63; D84; G15; 330; stock markets; heterogeneous speculators; exponential replicator dynamics; herding behavior; stylized facts